Two new species of Lefroyothrips (Thysanoptera: Thripinae) from China - Li, Yajin; Zhang, Hongrui (Zootaxa, 2024)
Two new species of Lefroyothrips are described from tropical areas in southern China: L. aliceae sp. n., and L. laurencei sp. n. An illustrated key to the three species of Lefroyothrips from China is also provided. All slide-mounted specimens are deposited at Yunnan Agricultural University.